Production and Analysis of Characteristics of Biodiesel Produced from Waste Cooking Oil - Farouk, Hazir; Husien, AbduAllah; Ali, Hazim; Osama, Samah (University of Khartoum Engineering Journal, 2022)
There is increasing interest on waste cooking oils (WCO) as a cost-effective feedstock for biodiesel production. In this study, a one-step transesterification process was adopted to produce biodiesel at a laboratory scale from waste cooking oil with a low level of free fatty acids (A.V. 1.09 mgKOH/g). The maximum biodiesel yield obtained was 85.3% when using a combination of process parameters of 25% (v/v) methanol to oil ratio, 0.8% (w/w) of KOH, a maintained reaction time of two hours, reaction temperature of 60o C, and a stirring speed of 400 rpm. In the quest to optimize the process parameters such as alcohol to oil molar ratio, and catalyst concentration, the results show that the biodiesel yield increases with the increase in methanol to oil molar ratio until the optimum ratio, then starts to decrease and it decreases if the alkali catalyst is added above an optimum concentration. The optimum values of methanol to oil molar ratio and alkali catalyst were 25% (v/v) and 0.8% (w/w), respectively. The basic physicochemical properties of the WCO biodiesel produced were found to be within the ASTM Standard D6751 specified limits for required parameters. The principal parameters were acid value, density, viscosity and flash point. The calorific value was found to be 41.05 MJ/kg.